Our Milky Way and other galaxies - Asimov, Isaac (Milwaukee : G. Stevens Pub., 1988)
Provides an insider's view of our own Milky Way and discusses the nature and behavior of galaxies in general.
Includes index.
Keywords: Galaxies -- Juvenile literature; Galaxies